MicroRNA-20b promotes cell growth of breast cancer cells partly via targeting phosphatase and tensin homologue (PTEN) - Zhou, Weidong (BioMed Central, 2014)
BACKGROUND: MicroRNAs (miRNAs) are endogenous, small non-coding RNAs that play important roles in multiple biological processes. MiR-20b has been reported to participate in breast cancer tumorigenic progression, however, the functional roles are still unclear and under debating. The aim of this study is to explicit the molecular mechanism of miR-20b underlying breast cancer tumorigenesis. RESULTS: In the present study, we showed that miR-20b was overexpressed in human breast cancer tissues and cell lines compared with paired adjacent normal tissues and normal cell lines, respectively. We identified PTEN, a well-known tumor suppressor, as the functional downstream target of miR-20b. Luciferase assays confirmed that miR-20b could directly bind to the 3′ untranslated region(UTR) of PTEN and suppress translation. Alteration of miR-20b expression changed PTEN protein level but not mRNA expression in ZR-75-30 and MCF-7 breast cancer cells, suggesting miR-20b regulates PTEN gene expression at the posttranscriptional level. Furthermore, upregulation of miR-20b significantly promoted the proliferation, colony formation and DNA synthesis of ZR-75-30 and MCF-7 breast cancer cells. Conversely, knockdown of miR-20b expression inhibited the growth of breast cancer cells in vitro and in vivo. CONCLUSION: Dysregulation of miR-20b plays critical roles in the breast cancer tumorigenesis, at least in part via targeting the tumor suppressor PTEN. This microRNA may serve as a potential diagnostic marker and therapeutic target for breast cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/2045-3701-4-62) contains supplementary material, which is available to authorized users.